Childhood stressful events, HPA axis and anxiety disorders - Faravelli, Carlo (Baishideng Publishing Group Co., Limited, 2012)
Anxiety disorders are among the most common of all mental disorders and their pathogenesis is a major topic in psychiatry, both for prevention and treatment. Early stressful life events and alterations of hypothalamic pituitary adrenal (HPA) axis function seem to have a significant role in the onset of anxiety. Existing data appear to support the mediating effect of the HPA axis between childhood traumata and posttraumatic stress disorder. Findings on the HPA axis activity at baseline and after stimuli in panic disordered patients are inconclusive, even if stressful life events may have a triggering function in the development of this disorder. Data on the relationship between stress, HPA axis functioning and obsessive-compulsive disorder (OCD) are scarce and discordant, but an increased activity of the HPA axis is reported in OCD patients. Moreover, normal basal cortisol levels and hyper-responsiveness of the adrenal cortex during a psychosocial stressor are observed in social phobics. Finally, abnormal HPA axis activity has also been observed in generalized anxiety disordered patients. While several hypothesis have attempted to explain these findings over time, currently the most widely accepted theory is that early stressful life events may provoke alterations of the stress response and thus of the HPA axis, that can endure during adulthood, predisposing individuals to develop psychopathology. All theories are reviewed and the authors conclude that childhood life events and HPA abnormalities may be specifically and transnosographically related to all anxiety disorders, as well as, more broadly, to all psychiatric disorders.